The Changing Economic Geography of Globalization - Vertova, Giovanna (Routledge Studies in Global Competition, 2006)
The process of globalization has had profound, often destabilizing, effects on space, at all levels (i.e. local, regional, national, international). This revealing book analyzes, both theoretically and empirically, the effects of globalization over space. It considers, through a dialogue among different paradigms, the ways in which space has become more important in the global economy. Globalization has been advocated as a way of shrinking time and space which will lead to a homogenized global market; a suggestion challenged in differing ways and with a variety of approaches by all the contributors to this volume. Leading authorities from a range of disciplines are represented amongst this impressive list of contributors, including Eric Sheppard, Bjørn Asheim, Richard Walker and Peter Swann. The chapters demonstrate persuasively the continuing, and even increasing, role of space in the global economy, and throughout, the book covers viewpoints from the fields of: international political economy economic geography regional and local economics. This impressive volume, which contains a selection of the best in contemporary scholarship, will be of interest to the international arena of academicians, policy makers and professionals in these or related fields.